Hak Asasi bagi Anak Berkebutuhan Khusus dalam Mendapatkan Pembelajaran pada Masa Pandemi Covid-19 di SLB Pelita Hati Tampan Pekanbaru - Cica Sri Yulia Ningsih; Said Suhil Achmad; Dafetta Fitrilinda (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Tujuan penelitian ini adalah mengetahui hak asasi anak berkebutuhan khusus dalam mendapatkan pembelajaran di SLB Pelita Hati Tampan, Pekanbaru. Bentuk studi yang diimplementasikan merupakan study deskriptif sekaligus menerapkan metode kualitatif, sehingga menjadikan studi ini termasuk ke dalam jenis penelitian kualitatif, yang dalam mengumpulkan datanya menggunakan 3 cara, yaitu observasi, wawancara, dan dokumentasi. Analisis menggunakan 4 cara yakni mengumpulkan data, reduksi data, menyajikan data, dan kesimpulan. Hasil penelitian ini didapat dari 3 indikator: mempertahankan, menghargai, dan menghormati. Temuan menunjukkan guru-guru di SLB Pelita Hati menghargai kekhususan anak dengan tetap memberikan pembelajaran dengan teknik-teknik yang memang diperuntukkan kepada anak berkebutuhan khusus. Getting learning also includes the right to the fulfillment of life, where it corresponds to the significance of human rights that are fundamental to the importance of non-discrimination and growth in the fulfillment of ones life. So it is with special-needs children who have the right to study at the time of pandemi covid-19. The purpose of this study is to know the human rights of special-needs children to be taught in SLB a handsome new liver lamp. The form of the study implemented in the study is a descriptive and qualitative study, making it include the kind of qualitative research, which is collecting the data using 3 ways, observation, interview, and documentation, which will then be reanalyzed using four ways, these are: collecting data, reduction data, presenting data, and finally drawing conclusions. The results of this study came from 3 indicators of maintaining, honoring, and honor, of which the three indicators were found in the study. What this study has found indicates that teachers in SLB lamps maintain special needs childrens specialness by honoring them with techniques intended for children with special needs, the teachers continue to respect them.